Effect of Premium Compost on Soil Carbon Microbial Biomass in Pineapple Plants on Marginal Land Central Lampung - Yusnaini, Sri; Aditya, Dinar; Ramadhani, Winih Sekaringtyas; Novpriansyah, Hery; Dermiyati, Dermiyati; Rivaie, Arivin (JOURNAL OF TROPICAL SOILS, 2024)
Acidic soil reactions, low nutrient content, low organic carbon levels, and low soil biodiversity characterize marginal land. Adding organic matter, such as compost, is expected to rehabilitate these lands. One key biological indicator of successful land rehabilitation by adding organic matter or compost is soil carbon microbial biomass (SCMB). This study aimed to assess the effect of compost on SCMB in pineapple plants. It was designed using a Randomized Completely Block Design with four treatments: Control (P0) = Without compost (Pineapple Cultivation Standard at GGPC), P1 = Cow dung compost (50 Mg ha-1), P2 = Premium compost A (50 Mg ha-1) and P3 = Premium compost B (50 Mg ha-1). Each treatment was replicated four times. The data were analyzed using ANOVA at the 5% significance level, following testing for homogeneity of variance using the Bartlett test and additivity with the Tukey test. Different treatment means were examined using contrast orthogonal tests, and correlation tests were performed to explore relationships among key variables. Results indicated that cow dung and premium compost (A and B) increased SCMB by 89.31% and 84.06%, respectively, at 15 and 16 MAP observations. At 16 MAP observations, soil organic carbon and soil pH were correlated with SCMB; in contrast, at observations 13, 14, and 15 MAP, soil organic carbon, soil pH, soil moisture, and soil temperature did not correlate with SCMB.